2014
DOI: 10.3168/jds.2014-8237
|View full text |Cite
|
Sign up to set email alerts
|

Diseases, reproductive performance, and changes in milk production associated with subclinical ketosis in dairy cows: A meta-analysis and review

Abstract: Many studies have shown that subclinical ketosis (SCK) is associated with an increased risk of developing various diseases, reproductive disorders, and changes in milk production. The present work aims at producing an overview between this disorder and theses outcomes. A meta-analysis of the literature, including 131 different models from 23 papers, or a review when the literature was scarce was conducted. For each outcome, the odds ratio (OR), relative risk, or hazard ratio was presented for various moderator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
180
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(211 citation statements)
references
References 45 publications
8
180
0
10
Order By: Relevance
“…In this study, plasma concentrations of BHBA in all treatments were found above the range of normal values for dairy cows (averaging 1.01 mmol/L), which are considered acceptable from 0.1 to 0.6 mmol/L in early lactation (Wittwer, 2012;Raboisson et al, 2014). Otherwise, values ≥0.6 mmol/L of BHBA are considered indicators of negative energy balance, and greater than 1.2 and/or 1.4 mmol/L are indicative of subclinical ketosis (Geishauser et al, 1998;Duffield et al, 2009;Cucunubo et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, plasma concentrations of BHBA in all treatments were found above the range of normal values for dairy cows (averaging 1.01 mmol/L), which are considered acceptable from 0.1 to 0.6 mmol/L in early lactation (Wittwer, 2012;Raboisson et al, 2014). Otherwise, values ≥0.6 mmol/L of BHBA are considered indicators of negative energy balance, and greater than 1.2 and/or 1.4 mmol/L are indicative of subclinical ketosis (Geishauser et al, 1998;Duffield et al, 2009;Cucunubo et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Subclinical ketosis is suspected when the serum BHB concentrations exceed 1.2 mmol/l according to some authors (Leblanc 2010, Suthar et al 2013, or 1.4 mmol/l according to others (Raboisson et al 2014). After calving in Holstein-Friesian and Polish Red cows, BHB levels significantly increased but their values seems to confirm no negative energy balance.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that transition dairy cows (cows in the period from three weeks before to three weeks after parturition) experience a negative energy balance (NEB) [37,38]. This arises from the increased energy demands at parturition, especially due to their genetic potential to produce high levels of milk.…”
Section: The Benefit Of Using Feed Supplements: Why the Feed Industrymentioning
confidence: 99%